2019
DOI: 10.1590/1516-3180.2018.0430140319
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals’ perception of patient safety culture in a university hospital in São Paulo: A cross-sectional study applying the Hospital Survey on Patient Safety Culture

Abstract: BACKGROUND: Patient safety culture is part of the organizational profile of healthcare institutions and is associated with better quality of care. OBJECTIVE: To assess patient safety culture in a university hospital. DESIGN AND SETTING: Hospital-based cross-sectional study conducted in a public university hospital in São Paulo, Brazil, between September and December 2015. METHODS: We randomly selected 68 sectors of the hospital, to include up to 5 employees from each sector, regardless of length of experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
1
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
6
10
1
9
Order By: Relevance
“…European studies also coincide with our findings regarding weaknesses [ 30 , 31 , 36 , 37 , 38 ], although some of them did identify the dimensions of the expectations and actions of the unit/service management or supervision, teamwork, or openness in communication as strengths [ 36 , 37 ]. The study carried out in 2014 in Croatia by Brborovic [ 31 ] recorded low scores for staffing and identified non-punitive responses to errors as the lowest rated dimension, attributing this result to ‘cultural guilt’ and the perception that errors should be punished—a conclusion also shared in the Italian study by Bagnasco [ 39 ] in 2011. International studies [ 1 , 39 , 40 , 41 , 42 , 43 ] showed very similar results to our own, identifying the same weaknesses and no strengths except, as in our study, for the teamwork dimension which came closest to the strength criteria. Other studies identified the same areas for improvement, but also identified strengths such as organizational learning/continuous improvement, teamwork, and management support [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…European studies also coincide with our findings regarding weaknesses [ 30 , 31 , 36 , 37 , 38 ], although some of them did identify the dimensions of the expectations and actions of the unit/service management or supervision, teamwork, or openness in communication as strengths [ 36 , 37 ]. The study carried out in 2014 in Croatia by Brborovic [ 31 ] recorded low scores for staffing and identified non-punitive responses to errors as the lowest rated dimension, attributing this result to ‘cultural guilt’ and the perception that errors should be punished—a conclusion also shared in the Italian study by Bagnasco [ 39 ] in 2011. International studies [ 1 , 39 , 40 , 41 , 42 , 43 ] showed very similar results to our own, identifying the same weaknesses and no strengths except, as in our study, for the teamwork dimension which came closest to the strength criteria. Other studies identified the same areas for improvement, but also identified strengths such as organizational learning/continuous improvement, teamwork, and management support [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of reported AEs was similar to other national and international work [ 1 , 22 , 28 , 36 , 40 , 41 ]. The perception of D1 was identified as an area for improvement in medical and mixed wards, while in surgical wards it was seen neither as a weakness or a strength.…”
Section: Discussionsupporting
confidence: 87%
“…There was a difference in the mean time spent working in the hospital and working time in the unit with the highest number of positive responses; longer working time in the profession represented better grades and fewer reported events (19) . In another study, a better safety culture was observed among more experienced employees, nurses and employees with less education (33) . It was observed, in a study, that the type of management, service unit, position and the number of incident reports directly influence patient safety culture (28) .…”
Section: Discussionmentioning
confidence: 86%
“…Galvão et al . (2018) and Okuyama et al . (2019) both conducted studies at Brazilian public hospitals.…”
Section: Discussionmentioning
confidence: 97%